Predation on black flies (Diptera: Simuliidae) by the carnivorous plant Pinguicula vulgaris (Lentibulariaceae) in northern Sweden - Adler, Peter; Malmqvist, Björn (Entomologica Fennica, 2004)
Adult back flies represented nearly 85% of 915 arthropods captured by the carnivorous plant Pinguicula vulgaris L. along a stream in northern Sweden. Two species, Cnephia eremites Shewell and Cnephia pallipes (Fries), accounted for more than 97% of the total number of captured black flies. By virtue of their large populations, site fidelity at lake outfalls, and concentrated activity near the ground, these flies provide a predictable supply of prey that could affect the fitness of streamside carnivorous plants.